Traditions in the formation of historical manor parks of the Poltava Region (Ukraine) - Shevchenko, Liudmyla; Novoselchuk, Natalia; Troshkina, Olena (Landscape Architecture and Art, 2022)
The article is devoted to the historical manor parks of one of the picturesque regions of Ukraine – Poltava Region. The focus of the study is on traditions and peculiarities of their formation, which developed historically in the period of the 18th-19th centuries. Historical-factual, monographic, stylistic, and comparative-historical methods were used during the research. The methods of theoretical analysis, visual inspection and graphic reconstruction were also applied. The article presents a brief history of the emergence of manor and park complexes in the region. Foreign and local specialists, who were involved in their formation, including park areas, are presented. Manor parks were distinguished by the nature of landscape design and planning composition. The article proves that the functional and planning composition of manor parks of the Poltava Region was based on the following structural elements: park (landscape), economic and production, greenhouse, and orchard zones. The main features of the solution of the Poltava Region historical manor parks were revealed. They consisted in the harmonious combination of a natural massif of greenery with created landscape groups, existing water sources with artificial ponds, and architectural buildings of estates. Traditionally, life in Poltava manors was mainly focused on calm rest and the development of agricultural (or industrial) productions’ branches. The landscape and hydrological characteristics of the area and the dendrological composition of the vegetation were the basis for the landscape-planning solution of manor parks. Local gardeners and gardening experts involved in the work tried to preserve and emphasize them. Manor parks continue to interest researchers as examples of garden and park art. Exquisite stylistic solutions, interesting landscape and dendrological compositions were tested on these private territories. Unique views and landscapes were created here.